HUBUNGAN KESEGARAN JASMANI DENGAN HASIL BELAJAR PADA SISWA KELAS V SDN 005 KERUMUTAN KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Rahimin '; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation of Students in class V of SDN 005 Kerumutan Pelalawan District. Researcher found the quality of learning outcomes of sport education still low. Evident from learning outcomes still below average or below standars that class rise to minimal completeness criteria. The purpose of this research is to see the contrubution of phsycal fitness with learning outcomes of students in clas V of SDN 005 Kerumutan Kerumutan District of Pelalawan. Population in this research are all students in class V amount 15 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 15 people. Research instrument used Indonesia phsycal fitness test and learning outcomes test from raport outcomes. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : there is correlation between of phsycal fitnesst (X) to the result of learning (Y) which shows rhitung = 0,567 >rtabel = 0,532.Key word : phsycal fitness, the result of learning